2014
DOI: 10.1016/j.jhealeco.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent health and adult labor market outcomes

Abstract: Whereas a large literature has shown the importance of early life health for adult socioeconomic outcomes, there is little evidence on the importance of adolescent health.We contribute to the literature by studying the impact of adolescent health status on adult labor market outcomes using a unique and large-scale dataset covering almost the entire population of Swedish males. We show that most types of major conditions have long-run effects on future outcomes, and that the strongest effects result from mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 44 publications
5
73
0
Order By: Relevance
“…These are roughly the same data as those used by Lindqvist and Vestman (2011) and by Lundborg et al (2014a). 4 The data include all individuals that enlisted for the Swedish army between 1969 and 1997 and that were born between 1950 and 1979.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These are roughly the same data as those used by Lindqvist and Vestman (2011) and by Lundborg et al (2014a). 4 The data include all individuals that enlisted for the Swedish army between 1969 and 1997 and that were born between 1950 and 1979.…”
Section: Datamentioning
confidence: 99%
“…Whereas older research has often focused on education, recent literature has shown the importance of health, cognitive ability and non-cognitive abilities (e.g., Heckman et al 2006;Currie et al 2010;Lindqvist and Vestman 2011;Lundborg et al 2014a). In this paper, we examine if those with poor health and abilities face a "double penalty" in the sense that they are not only less likely to be employed in general, but their probability of employment is also more sensitive to the unemployment rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oreopoulos et al, 2008;Lundborg et al, 2014). This literature indicates that poor child health predicts inferior adult socio-economic status (SES) 1 , commonly measured by education, income and occupation.…”
Section: Introductionmentioning
confidence: 99%
“…There is also considerable evidence on correlations between child health and individual labor market outcomes (e.g. Lundborg et al, 2014). According to Smith (2009a) poor child health affects total household labor income not only via individual earnings and labor supply but also via assortative mating and spousal labor market 17 We construct this measure in line with Angerer and Lam (2009).…”
mentioning
confidence: 99%